The Effect of Progressive Muscle Relaxation on Fatigue Levels in Patients Undergoing Hemodialysis - Faradhita Afira Octa Priheningtyas; Syahruramdhani Syahruramdhani; Tariyah Tariyah (An Idea Health Journal, 2025)
Introduction: Chronic kidney disease (CKD) is a disease development from acute kidney failure that is progressive and slow which usually lasts for a long time, causing the kidneys to lose their ability to maintain the composition and amount of fluid in a normal state. Hemodialysis is a therapy that can improve the condition of patients with chronic kidney failure, but on the other hand this treatment method also makes patients have to face various problems, one of which is fatigue. The purpose of this study was to determine the effect of Progressive muscle relaxation on the level of fatigue in patients undergoing hemodialysis. The method used in this intervention study was a case study with a quantitative descriptive approach by evaluating the implementation of the Progressive muscle relaxation intervention. The instrument for measuring the level of fatigue used the FACIT-fatigue scale questionnaire. The results of this study showed that in the initial assessment the patient experienced severe fatigue with a score of 11 and after being given Progressive muscle relaxation intervention, the patient's fatigue score became 24, which is moderate fatigue. From the results of this study it can be concluded that there is an effect of giving Progressive muscle relaxation on reducing the level of fatigue in patients undergoing hemodialysis.